Analisis Tindak Tutur Ilokusi dalam Dialog Film Animasi Meraih Mimpi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The film Meraih Mimpi is one of the animated films that is the pride of the Indonesian film industry. This film is the first three-dimensional (30) wide-screen animated film in Indonesia by local children produced by Infinite Frameworks (IFW), an animation studio based in Batam. This study examines illocutionary speech acts. The researcher used the animated film “Meraih Mimpi” as a data source. In this film, the implied message to be conveyed is not to rush into believing information obtained and not to be easily provoked by other people's words that are not necessarily true. The theory of speech acts is considered very important in communicating, both directly and indirectly. From the discussion above, it was found that speech acts in the animated dialogue film Meraih Mimpi, the types of illocutionary speech acts in the animated dialogue film Meraih Mimpi found in this study include: Assertive speech acts, Directive speech acts, Commissive speech acts, Expressive acts, and Declarative speech acts. Based on data analysis, there are assertive, directive and expressive speech acts that are most often found in the speech of the animated dialogue film Meraih Mimpi. This is in accordance with the theme raised in the film Meraih Mimpi which is educational. Inviting and wanting the audience to follow the moral message contained in the story of the film. The functions of illocutionary speech acts in the animated dialogue film Meraih Mimpi were found in this study, including: Competitive function, Fun function, Cooperation function, and Differentiating function. Based on data analysis, there are competitive functions and fun functions that are most often found in the speech of the animated dialogue film Meraih Mimpi. This is in accordance with the genre raised in the film Meraih Mimpi, namely animation that provides an interesting nuance and an entertaining impression. The theme raised in the film is appropriate because it is able to provide education for those who watch it.